2022
DOI: 10.3389/fimmu.2022.930141
|View full text |Cite
|
Sign up to set email alerts
|

Immune-mediated inflammatory diseases with chronic excess of serum interleukin-18

Abstract: Review: Interleukin-18 (IL-18) is a proinflammatory cytokine that promotes various innate immune processes related to infection, inflammation, and autoimmunity. Patients with systemic juvenile idiopathic arthritis and adult-onset Still’s disease exhibit chronic excess of serum IL-18, which is associated with a high incidence of macrophage activation syndrome (MAS), although the mechanisms of IL-18 regulation in such diseases remain largely unknown. Similar elevation of serum IL-18 and susceptibility to MAS/hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 128 publications
0
6
0
Order By: Relevance
“…As a readout of inflammasome activation in vivo ( 45 ), we next measured IL-18 levels in patient plasma. Circulating IL-18 was elevated in this cohort, being above the reference range in 55% of MF patients ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…As a readout of inflammasome activation in vivo ( 45 ), we next measured IL-18 levels in patient plasma. Circulating IL-18 was elevated in this cohort, being above the reference range in 55% of MF patients ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon reflects the clinical intersubject variability within the p.Tyr64Cys variant group and possible overlap with C-terminal variants in the CDC42 gene and highlights that the p.Tyr64Cys variant does support the hypothesis that the gene is associated with distinct diseases. The clinical phenotypes related to C-terminal variants are characterized by severe neonatal-onset dyshematopoiesis and immune dysregulation including autoinflammation, rash, and HLH (NOCARH syndrome) ( Gernez et al, 2019 ; Lam et al, 2019 ; He et al, 2020 ; Coppola et al, 2022 ) with a chronic excess of the inflammatory cytokine, IL-18 as a hallmark of these disorders ( Miyazawa and Wada, 2022 ; Shimizu et al, 2022 ). A similar phenotype distinguished by the hyperinflammatory state, full-blown HLH, and hitherto not reported, development of non-Hodgkin lymphoma has also been described by our group in the patient with a novel p.Cys81Tyr variant ( Szczawińska-Popłonyk et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Amongst actinopathies, WDR1 disease has been recently described. It is characterized by autoinflammatory features, including recurrent stomatitis, difficult wound healing and immunodeficiency; [ 84 ] WD repeat-containing domain 1 (WDR1) is an actin regulatory protein that promotes cofilin-dependent actin filament turnover [ 85 ]. In 2015, Kim et al observed that inflammation in WDR1 patients is driven by IL-18, and this mechanism reinforces the concept that the IL-18 is induced through aberrant actin depolymerization-driven pyrin inflammasome activation [ 86 ].…”
Section: Il-18 In Autoinflammatory Diseasesmentioning
confidence: 99%
“…Given the high mortality rate associated with the MAS condition, we believe that further clinical trials of IL-18BP and anti-IL-18 antibodies are urgently needed. Finally, the use of drug therapies that specifically focus on IL-18 inhibition, in addition to the inhibition of IL-1β, represents a new therapeutic approach and preliminarily appears to be safe and effective [ 85 , 93 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%